Aggregation induced emission luminogen bacteria hybrid bionic robot for multimodal phototheranostics and immunotherapy - Liwei Zhu; Guangjie Song; Wentian Zhang; Yifan Wu; Yuling Chen; Jiayi Song; Deliang Wang; Guoxin Li; Ben Zhong Tang; Ying Li (Nature Communications)
Abstract Multimodal phototheranostics utilizing single molecules offer a “one-and-done” approach, presenting a convenient and effective strategy for cancer therapy. However, therapies based on conventional photosensitizers often suffer from limitations such as a single photosensitizing mechanism, restricted tumor penetration and retention, and the requirement for multiple irradiations, which significantly constrain their application. In this report, we present an aggregation-induced emission luminogen (AIEgen) bacteria hybrid bionic robot to address above issues. This bionic robot is composed of multifunctional AIEgen (INX-2) and Escherichia coli Nissle 1917 (EcN), i.e., EcN@INX-2. The EcN@INX-2 bionic robot exhibits near-infrared II (NIR-II) fluorescence emission and demonstrates efficient photodynamic and photothermal effects, as well as tumor-targeting capabilities. These features are facilitated by the complementary roles of INX-2 and EcN. The robot successfully enables in vivo multimodal imaging and therapy of colon cancer models in female mice through various mechanisms, including the activation of anti-tumor immunity, as well as photodynamic and photothermal therapy. Our study paves an avenue for designing multifunctional diagnostic agents for targeted colon cancer therapy through image-guided combinational immunotherapy.